Implementation of Education and Discipline Characteristics of Students at SMA Muhammadiyah 3 Tulangan - Muhammad Rafly Fitrawantono (Proceedings of The ICECRS, 2021)
The purpose of this scientific work is to find out how the implementation of student discipline character education at SMA Muhammadiyah 3 Tulangan during the pandemic. In the research process this time using data collection and observation techniques. Based on the results of research, the character of the discipline of students is very good to emulate. That is, by applying reading the Koran before the learning process begins and it must be followed by both students from grades ten to twelve to educators. Education carried out at SMA Muhammadiyah 3 Tulangan during the covid-19 pandemic was carried out online